An experimental investigation of resuspension due to walking - Lin, Yi Jie. (2011)
The behaviour of aerosol contaminants is crucial to the biological welfare of the human population. Deadly diseases can be transmitted via airborne particles. When aerosol contaminants are introduced into an enclosed indoor environment, it might remain as airborne particles or settle down and deposit onto interior surfaces. There is also a possibility of attaching itself to dust particles that are already present. Human beings spend most of their time indoors whether at work or at home. Studies done by Wallace (1996) showed that exposure to micro sized particulate matter is prominent in these indoor environments. Inhalation of such particulates lead to respiratory diseases like asthma and also allow infectious disease to roam around when they attach themselves to dust particles.